The Effectiveness of Oxytocin Massage on Milk Production in Postpartum Mothers - Anita Lontaan; Moudy Lombogia; Teresia Retna Puspitadewi (Bulletin of Inspiring Developments and Achievements in Midwifery, 2025)
Background: Exclusive breastfeeding is essential for supporting optimal infant growth and development, as breast milk provides complete nutrients and enhances the immune system. However, many postpartum mothers experience difficulties in breast milk production due to physical and psychological factors. Oxytocin stimulation through massage is considered a potential method to improve milk flow. This study aimed to determine the effectiveness of oxytocin massage on milk production among postpartum mothers in the working area of Andalas Padang Health Center. Methods: This study used a quantitative approach with a pretest–posttest experimental design. The research was conducted in the working area of Andalas Padang Health Center with a sample of 30 postpartum mothers selected based on inclusion and exclusion criteria. Data were collected through interviews and observations, and analyzed using univariate and bivariate analysis with a paired t-test to assess differences before and after the intervention. Results: The findings showed that 90% of respondents experienced improved milk production after receiving oxytocin massage. The t-test results indicated a significant difference in milk production before and after the intervention (p < 0.05). Conclusion: Oxytocin massage is effective in improving milk production in postpartum mothers and can support the success of exclusive breastfeeding.